2010
DOI: 10.1152/ajpregu.00808.2009
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and the kidney

Abstract: Connexins (Cxs) are widely-expressed proteins that form gap junctions in most organs, including the kidney. In the renal vasculature, Cx37, Cx40, Cx43, and Cx45 are expressed, with predominant expression of Cx40 in the endothelial cells and Cx45 in the vascular smooth muscle cells. In the tubules, there is morphological evidence for the presence of gap junction plaques only in the proximal tubules. In the distal nephron, Cx30, Cx30.3, and Cx37 are expressed, but it is not known whether they form gap junctions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
151
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 137 publications
6
151
1
3
Order By: Relevance
“…Exogenous H 2 S can protect against diabetes-induced hypertrophyand myocardialfibrosis, dysfunction, oxidative stress,apoptosis. 16,17 The pathological change of renal fibrosis exists in the whole course of the occurrence and development of DN; its manifestations include increase of collagenous fiber elements of extracellular matrix in mesangial cells, increase of collagen in renal tubule basement membrane and increase of renal tubule interstitial collagen and fibronection secretion. Collagen II is an important component of ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous H 2 S can protect against diabetes-induced hypertrophyand myocardialfibrosis, dysfunction, oxidative stress,apoptosis. 16,17 The pathological change of renal fibrosis exists in the whole course of the occurrence and development of DN; its manifestations include increase of collagenous fiber elements of extracellular matrix in mesangial cells, increase of collagen in renal tubule basement membrane and increase of renal tubule interstitial collagen and fibronection secretion. Collagen II is an important component of ECM.…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of GJs in the kidney has long been known, details on their function in the proximal tubule are sparse. Studies on renal vasculature have confirmed a role for various connexins in renin secretion and the regulation of blood pressure [31], but minimal data exist on their role in tubular function, where levels are also high. The novel findings presented here demonstrate a link between high glucose, TGF-β1, impaired cell adhesion and reduced GJ abundance in the proximal tubule.…”
Section: Introductionmentioning
confidence: 99%
“…Cx37 is expressed in monocytes/macrophages, platelets, kidney, and ovaries, but it is more abundant in endothelial cells in the blood vessels (7)(8)(9). However, Cx37 deletion does not impair vascular function because Cx40, which is also expressed in endothelial cells, can compensate for the absence of Cx37 (10,11).…”
mentioning
confidence: 99%